PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PADA PEMERINTAH KOTA BALIKPAPAN - Rudy Pudjut Harianto (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2021)
This research aims to analyze the influence of Regional Taxes, Regional Retribution, and Special Allocation Funds toward of Capital Expenditure at City Government of Balikpapan. Data Analyse method that used in this research are Multiple Linier Regression Analyse (correlation coeficient, determination coeficient, simultaneous test/F test, and partial test/t test). Accumulatively, coeficient correlation (R)= 0,733 so that it can be said that the independent variables toward dependent variable in this research can giving the strength correlation. Result of determination coefficient (R2)= 0,261 it can be said the independent variables can be explain the dependent variable of equal to 26,1% only. While the rest equal to 73,9% explained by other variable from outside model. The result of simultaneous test could be explained: variables of Regional Taxes, Regional Retribution, and Special Allocation Funds simultaneously have no effect on the Capital Expenditure variable. The result of significantion test could be explained:(1) Regional Taxes variable have no effect on the Capital Expenditure variable;(2) Regional Retribution variable have no effect on the Capital Expenditure variable; and (3) Special Allocation Funds variable have no effect on the Capital Expenditure variable.